Pengujian prestasi aplikasi sistem maklumat geografi berasaskan web bagi kajian kes penggunaan pelayan peta mapguide - Idris, Nurul Hawani (2008)
The internet has revolutionized the means of accessing and disseminating geospatial information in typical Geographic Information System (GIS) applications. However, the earlier design of internet is only to disseminate text-based information. When it comes to geospatial data handling, this architecture is no longer effective and needs proper enhancement towards providing acceptable level of performance both in information retrieval and rendering. Furthermore, the fact that many aspects might affect and causes bottlenecks of typical web application performance present new challenges for GIS developers to ensure a high quality service of their application. Hence, this research is carried out to study the issue (i.e. the performance of web GIS application). The performance testing is conducted to measure the response time in retrieving and rendering the spatial data for an application developed using Autodesk’s MapGuide as a map server. These tests are carried out using Web Application Stress Tool, which is a software designed for load simulations and response time measurements. Performance factors tested include map viewer types (Java and ActiveX) and geospatial data formats (MapGuide’s SDF and ESRI’s Shapefile). For each of these factors, the measurements of response time are made against the client connection types (28k and 56k) and the number of concurrent client access (1, 5, 25, 50 and 75 users). The results show that SDF format performs 52 percent faster in retrieving and rendering processes of geospatial data. Moreover, the ActiveX viewer performs faster in rendering data compared to Java. However, neither viewers show significant performance difference while handling information retrieval. The results of this study can be used as guidance for selecting geospatial data formats and types of map viewer that will results in the best performance particularly in a client-side web-based GIS application.